Recombinant Human Kallistatin Inhibits Angiogenesis by Blocking VEGF Signaling Pathway. Issue 3 (March 2014) - Huang, K.F.; Yang, H.Y.; Xing, Y.M.; Lin, J.S.; Diao, Y.
ABSTRACT Kallistatin has been recognized as an endogenous angiogenic inhibitor. However, the underlying molecular mechanism remains poorly understood. Taking it into account that vascular endothelial growth factor (VEGF) has been implicated in all aspects of normal and pathological vasculogenesis and angiogenesis. In this study, we investigated whether VEGF signaling pathway was impacted by the anti‐angiogenic effect of recombinant human kallistatin (rhKal). We found that the rhKal inhibited proliferation as well as induced apoptosis of cultured human umbilical vein endothelial cells (HUVECs) in both concentration‐ and time‐dependent manners. The rhKal also suppressed the VEGF‐induced migration and tube formation of HUVECs. Furthermore, our data revealed that the rhKal suppressed the VEGF165‐stimulated tyrosine phosphorylation of VEGFR‐2 as well as its downstream signal molecular activation. The inhibition of receptor phosphorylation was correlated with a decrease in VEGF‐triggered phosphorylation of angiogenesis signal molecules AKT and ERK, but not stress‐related JNK. Taken together, these findings added the knowledge for us to understand the anti‐angiogenic mechanism of kallistatin, which suggested that the rhKal could be worth as a candidate compound for further development for the purpose of anti‐angiogenic therapies. J. Cell. Biochem. 115: 575–584, 2014. © 2013 Wiley Periodicals, Inc.